2016
DOI: 10.1177/1591019916665346
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and value of preoperative embolization of a congenital choroid plexus tumour in the premature infant: An illustrative case report with technical details

Abstract: We present a case of a preterm boy (born at 35 weeks of pregnancy) who was delivered urgently by a caesarean section due to placental abruption. The baby was found to have a tense fontanelle leading to imaging that showed a 5.5 cm right intraventricular mass centred in the atrium, hydrocephalus and extensive surrounding vasogenic oedema. The mass was avidly enhancing with a few large associated vessels suggesting high vascularity. The condition of the baby was acutely deteriorating. He had multiple se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Forty full-text articles were evaluated. Eighteen articles were finally included for analysis (Table 1; Figure 4) (1,3,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The majority of the articles were case reports, and included a total of 30 cases with a pathological diagnosis of CPP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty full-text articles were evaluated. Eighteen articles were finally included for analysis (Table 1; Figure 4) (1,3,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The majority of the articles were case reports, and included a total of 30 cases with a pathological diagnosis of CPP.…”
Section: Resultsmentioning
confidence: 99%
“…MRI shows equal or low T1 signal and high T2 signal ( 2 ). In addition to surgical removal of the tumor, cerebrospinal fluid shunts or interventional embolization can be performed preoperatively ( 10 ). The most common surgical treatment for CPP is transcortical approach by a microscope ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival with surgical resection alone approximates 95% in this age group (Table 1). When the tumor embolization regimen was added to two CPP cases prior to surgery, both infants survived [3]. Siegfried et al reported similar survivals (100%) in 54 CPPs under the age of 18 [67].…”
Section: Treatment and Outcomementioning
confidence: 96%